1999
DOI: 10.1097/00005768-199904000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast responses to variation in soft tissue mobilization pressure

Abstract: The morphological evidence indicated that the application of heavy pressure promoted the healing process to a greater degree than light or moderate pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
182
1
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(207 citation statements)
references
References 16 publications
4
182
1
3
Order By: Relevance
“…20 ASTYM has been shown to cause increased fibroblast recruitment and activation in rat tendons which should theoretically promote proper healing, but this has not been thoroughly studied in humans. [21][22][23] ASTYM treatment is thought to activate a regenerative response in soft tissues via induction of leakage from dysfunctional capillaries which leads to fibroblast activation, macrophage mediated phagocytosis, and a local release of growth factors. [20][21][22][23][24] While eccentric exercise and ASTYM should theoretically be useful in the management of HHT, the research supporting both of these interventions is lacking and there are no studies that have reported the effects of a combined treatment approach.…”
Section: 13mentioning
confidence: 99%
“…20 ASTYM has been shown to cause increased fibroblast recruitment and activation in rat tendons which should theoretically promote proper healing, but this has not been thoroughly studied in humans. [21][22][23] ASTYM treatment is thought to activate a regenerative response in soft tissues via induction of leakage from dysfunctional capillaries which leads to fibroblast activation, macrophage mediated phagocytosis, and a local release of growth factors. [20][21][22][23][24] While eccentric exercise and ASTYM should theoretically be useful in the management of HHT, the research supporting both of these interventions is lacking and there are no studies that have reported the effects of a combined treatment approach.…”
Section: 13mentioning
confidence: 99%
“…A indicação da cirurgia somente deve ser feita após seis meses naqueles casos em que não ocorrer melhora dos sintomas com o tratamento clínico (64)(65)(66) . A cirurgia da tendinopatia patelar crônica geralmente apresenta, em média, 75 a 85% de bons resultados, mas essa percentagem varia de 40 a 100% (67) . Como a fisiopatologia geralmente não é bem definida, a técnica cirúrgica escolhida baseia-se na opinião e experiência do cirurgião (25) .…”
Section: Tratamento Conservadorunclassified
“…Recovery after tendinosis may be accelerated with injections of CDMP. Since tendons injected with collagenase (Gehlsen et al 1999), carrageenan (Kurtz et al 1999) or PGE1 (Sullo et al 2001) in rats develop symptoms of tendinosis, it would be interesting to evaluate the effect of CDMP-2 in one of these models.…”
Section: Resultsmentioning
confidence: 99%